The stages and trends in the study of algae of Left-Bank Polissya (Ukraine) - Жежера, М. Д. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The retrospective review of the algal study of Left-bank part of the Ukrainian Polissya (LP) has been presented. In more than 100-year period (1870–2010) in LP waters and soils 1281 species (1603 infraspecific taxa) algae from 11 divisions were revealed. The majority of found species belong to Chlorophyta, Bacillariophyta, Cyanoprokaryota and Euglenophyta. The other divisions are represented by far less number of species. These studies included floral, systematic, ecological, coenotic and applied researches.